Simulation of Vertical Thin-Film Solar Battery under Exposure of Concentrated Solar Radiation - A. K. Esman; G. L. Zykov; V. A. Potachits; V. K. Kuleshov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Solar energy is one of the most important and promising energy sectors in the world. Batteries that convert sunlight into electrical energy could become a replacement for traditional carbon-based energy sources. Vertical thin-film solar batteries are one of the new approaches to solar energy generation. The vertical configuration of solar panels provides maximum absorption of sunlight throughout the day. This orientation allows the batteries to capture solar energy even at low angles of incidence of the sun’s rays, which prolongs their operating time and improves the efficiency of electricity production. In this work, the authors proposed a three-dimensional model of a vertically oriented solar battery, as well as they calculated and evaluated the temperature characteristics and the efficiency obtained under conditions of changing ambient temperature. Herewith the power densities of concentrated solar radiation with maximum values from 1 to 10 kW/m2 were varied. The distribution of the maximum values of the surface temperature of the solar battery has been studied. Also, the dependences of the maximum values of the solar battery temperature and the temperature gradient inside it, as well as the dependences of the minimum and maximum values of the heat flux from the solar battery surface on the time of day in the middle of January and July have been studied and plotted. As the calculations have shown, the maximum values of the temperature gradient inside the solar battery in January are ~47–50 % higher than in July. The potential difference, generated by the battery, reaches its maximum values from 11 a.m. to 4 p.m. both in January and July. The use of vertical thin-film solar batteries will improve the power generation efficiency and lower operating costs by reducing the influence of dust, rain and snow.